2021
DOI: 10.5194/soil-7-639-2021
|View full text |Cite
|
Sign up to set email alerts
|

Heterotrophic soil respiration and carbon cycling in geochemically distinct African tropical forest soils

Abstract: Abstract. Heterotrophic soil respiration is an important component of the global terrestrial carbon (C) cycle, driven by environmental factors acting from local to continental scales. For tropical Africa, these factors and their interactions remain largely unknown. Here, using samples collected along topographic and geochemical gradients in the East African Rift Valley, we study how soil chemistry and fertility drive soil respiration of soils developed from different parent materials even after many millennia … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 79 publications
1
11
0
Order By: Relevance
“…Similarly, our data on the chemical composition (C : N ratios) of living canopy leaves (Fig. S5) and the findings of Bukombe et al (2021) provide further support for the notion that nutrient-limited systems tend to develop plant traits that are typically signs of resource conservation strategies (Grau et al, 2017;Urbina et al, 2021) while accumulating comparably thick litter layers (Fig. 2a,b) and thick O-horizons (Fig.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Similarly, our data on the chemical composition (C : N ratios) of living canopy leaves (Fig. S5) and the findings of Bukombe et al (2021) provide further support for the notion that nutrient-limited systems tend to develop plant traits that are typically signs of resource conservation strategies (Grau et al, 2017;Urbina et al, 2021) while accumulating comparably thick litter layers (Fig. 2a,b) and thick O-horizons (Fig.…”
Section: Discussionsupporting
confidence: 79%
“…Soil C stocks in tropical African forests have been shown to be determined predominantly by the potential of soils to stabilize C by these organo‐mineral associations (Kirsten et al ., 2021; Reichenbach et al ., 2021). Recent studies from tropical African montane forests, for example, have demonstrated that geochemical soil properties related to the local parent material explain up to 75% of variability in SOC stocks (Reichenbach et al ., 2021) and were significant in explaining soil C turnover under stable, warm‐humid atmospheric conditions (Bukombe et al ., 2021). Thus, drivers of NPP and the associated C fluxes in tropical forest systems remain unclear, as they crucially rely on the complex interplay of soil formation and nutrient availability, topography, climate, and biology (Yoo & Mudd, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Using the same soils as used in this study, Bukombe et al. (2021) showed that soil fertility constraints (e.g., pH KCl , base saturation, exchangeable acidity) are important drivers of C decomposition. In our study, regression analysis showed that soil acidity and exchangeable cations were the most important controls on microbial C acquisition as indicated by vector length (Table 2) although explained variance was relatively small ( R 2 = 0.12, RMSE = 1.32).…”
Section: Discussionmentioning
confidence: 99%
“…Soils were incubated in the dark at 20°C, which is a common temperature for incubation studies and for studies dealing with enzyme activity over larger environmental gradients (e.g., Craine et al., 2010; Schädel et al., 2020). Thereafter, all jars were closed periodically after every 2 (for topsoils) and 7 days (for subsoils) to allow for CO 2 accumulation over a period of 120 days (Bukombe et al., 2021). The end of the 4‐day pre‐incubation period is referred to in this study as ‘pre‐incubation’, while the end of the 120‐day incubation (without counting the 4 days of pre‐incubation) is referred to as ‘post‐incubation’.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation